PENGARUH BIJI KELOR (Moringa oleifera Lam) SEBAGAI KOAGULAN DARI BERBAGAI KETINGGIAN TEMPAT TUMBUH TERHADAP KUALITAS AIR SUNGAI PALU - Waluyo, Subur; Sangadji, Muh. Nur; Alam, Nur (AGROTEKBIS, 2018)
The aim is  to determine the effect of moringa seeds as coagulant harvested at various grow altitudes on water quality of the river and to get the best moringa seeds as coagulant that gives the best effect on the quality of palu river water. This study uses a completely randomized design (CRD) pattern of the factors that altitude grow consisting of 4 levels of elevation which is 36, 177, 340 and 639 m above sea level. Each treatment was repeated 4 times to obtain 16 experimental units. The data were analyzed statistically using variant analysis (ANOVA). If the treatment shows the significant effect or very significant continued with Test Honestly Significant Difference (HSD) at level 5 or 1 percent. The results showed that the coagulant moringa seeds were harvested at various grow altitudes showed very sgnificant effect on the quality of river water (pH, electrical conductivity, turbidity and total dissolved solids). Coagulant Moringa seeds of altitude grow 36 m above sea level provides the highest percentage increase of the quality of river water that lowers the pH of river water by 8.24, electrical conductivity 50.40%, turbidity 58.91% and 47.39% total dissolved solids